Short-term effects of particle size fractions on circulating biomarkers of inflammation in a panel of elderly subjects and healthy young adults - Hassanvand, Mohammad Sadegh; Naddafi, Kazem; Kashani, Homa; Faridi, Sasan; Kunzli, Nino; Nabizadeh, Ramin; Momeniha, Fatemeh; Gholampour, Akbar; Arhami, Mohammad; Zare, Ahad; Pourpak, Zahra; Hoseini, Mohammad; et al. (Environmental Pollution, 2017)
Systemic inflammation biomarkers have been associated with risk of cardiovascular morbidity and mortality. We aimed to clarify associations of acute exposure to particulate matter (PM10 (PM < 10 μm), PM2.5-10 (PM 2.5–10 μm), PM2.5 (PM < 2.5 μm), PM1-2.5 (PM 1–2.5 μm), and PM1 (PM < 1 μm)) with systemic inflammation using panels of elderly subjects and healthy young adults. We followed a panel of 44 nonsmoking elderly subjects living in a retirement home and a panel of 40 healthy young adults living in a school dormitory in Tehran city, Iran from May 2012 to May 2013. Blood biomarkers were measured one every 7–8 weeks and included white blood cells (WBC), high sensitive C-reactive protein (hsCRP), tumor necrosis factor-soluble receptor-II (sTNF-RII), interleukin-6 (IL-6), and von Willebrand factor (vWF). We measured hourly indoor and outdoor exposure to PM10, PM2.5-10, PM2.5, PM1-2.5, and PM1 mass concentration to derive weighted averages of personal exposure based on simultaneously collected time-activity data. The random intercept linear mixed effects model was used for data analysis. We observed significant positive associations for WBC and IL-6 with exposure to PM10, PM2.5-10, PM2.5, PM1-2.5, and PM1; sTNF-RII with PM2.5, PM1-2.5, and PM1; hsCRP with PM2.5 and PM1; and vWF with PM10 and PM2.5-10, PM2.5, and PM1-2.5 mass concentration in elderly subjects from the current-day and multiday averages. For healthy young adults, we found significant positive associations for WBC and IL-6 with exposure to PM10, PM2.5-10, PM2.5, and PM1-2.5, but no with PM1. The results showed that increase of hsCRP, sTNF-RII, and vWF were not significantly associated with any of the PM sizes investigated in the healthy young subjects. Our results provided some evidence that short-term exposure to PM10, PM2.5-10, PM2.5, PM1-2.5, and PM1 was associated with inflammation and coagulation blood markers, but associations were depended on PM size and also differed across the various time lag. [Display omitted] •Repeated measurements of PM exposure and circulating biomarkers were carried out in Iran.•Exposure to PM increases inflammatory and coagulation biomarkers both in elderly subjects and healthy young adults.•Associations were stronger in the elderly subjects.•Results confirm the hypothesis of PM induced pulmonary inflammation and oxidative stress.